English movies: Effects of l1/l2 subtitles on ESL learner’s listening comprehension and vocabulary - Ng, Yi Ru (2024)
This study looks into the effects of different types of subtitles—first language (L1), second language (L2), and no subtitles—on Malaysian university students' listening comprehension and vocabulary development. A mixed-method research strategy including an experimental study and semi-structured interviews was used. The sample consisted of foundation and undergraduate students from Universiti Tunku Abdul Rahman (UTAR) who were native Chinese speakers with intermediate English skills. The experimental study exposed students to a short film with either L1 subtitles, L2 subtitles, or no subtitles, followed by a listening comprehension and vocabulary test. The semi-structured interviews explored students' perspectives on the effectiveness of subtitles in enhancing language skills. The experimental study's findings revealed that there is a significant difference between the test score among the groups. The students who watched the short video with L2 subtitles scored much better on the listening comprehension and vocabulary test than the other two groups. Interviews revealed that, while both types of subtitles were useful to students, L1 subtitles were more successful for listening comprehension and L2 subtitles for vocabulary acquisition. Personal preferences differed, with some students preferring L1 subtitles for improved comprehension. The study explores the effectiveness of subtitles as a tool for improving listening comprehension and vocabulary acquisition. Future research should look at the impact of subtitles on a larger, more diverse population, as well as longitudinal studies, to acquire a more complete understanding of their effects on language acquisition.